A Time Off Incentive Was Not Associated with Influenza Vaccination Acceptance among Healthcare Workers. (26th June 2013) - Cheema, Saima; Vinnard, Christopher; Foster-Chang, Sarah; Linkin, Darren R.
Abstract : Objectives . The national influenza vaccination rate among healthcare workers (HCWs) remains low despite clear benefits to patients, coworkers, and families. We sought to evaluate formally the effect of a one-hour time off incentive on attitudes towards influenza vaccination during the 2011-2012 influenza season. Methods . All HCWs at the Philadelphia Veterans Affairs (VA) Medical Center were invited to complete an anonymous web-based survey. We described respondents' characteristics and attitudes toward influenza vaccination and determined the relationship of specific attitudes with respondents' acceptance of influenza vaccination, using a 5-point Likert scale. Results . We analyzed survey responses from 154 HCWs employed at the Philadelphia VA Medical Center, with a response rate of 8%. Among 121 respondents who reported receiving influenza vaccination, 34 (28%, 95% CI 20–37%) reported agreement with the statement that the time off incentive made a difference in their decision to accept influenza vaccination. Conclusions . Our study provides evidence that modest incentives such as one-hour paid time off will be unlikely to promote influenza vaccination rates within medical facilities. More potent interventions that include mandatory vaccination combined with penalties for noncompliance will likely provide the only means to achieve near-universal influenza vaccination among HCWs.